PERTANGGUNGJAWABAN PIDANA ANAK YANG MELAKUKAN TIDAK PIDANA YANG MENYEBABKAN MATINYA ORANG LAIN (Putusan Pengadilan Negeri Maumere No.2/Pid.Sus-Anak/2021/PN MME) - Raja Sareng, Yohanes Alfridson; Leo, Rudepel Petrus; Kadja, Thelma S M (Petitum Law Journal, 2024)
Children as legal subjects are not only victims but children are also not immune from being perpetrators of criminal acts. One of the cases in the decision of the Maumere District Court Number 2/PID.SUS-ANAK/2021/PN MME contains the criminal act of a child causing the loss of another person's life. In the decision. This type of research is Normative Legal Research. The type of approach used by the author in this research is the case approach, especially regarding cases that have been decided as can be seen in the jurisprudence regarding the cases that are the focus of the research. According to the author, imposing prison sentences on child perpetrators is inappropriate. This is because the author feels that the judge did not look at the best interests of the children and the condition of the children in conflict with the law at the time of the incident. According to the author, the best punishment in this case is supervision. Placing children in conflict with the law in prison at the Sikka Regency Detention Center is completely inconsistent with the law and is also for the sake of the child's future. The author's advice, increasing coordination between law enforcement officers, improving infrastructure, increasing professional law enforcement officers in the juvenile criminal justice process are important factors in the effective law enforcement process for children in conflict with the law.